Хмель, сон и явь. - Горелов П. Г. (Школьная библиотека, 1991)
Экземпляры: Селтинская районная библиотека (к/х) (20200811) / Инвентарный номер: 162368 / Авт.знак: Х 65 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6